2013
DOI: 10.7860/jcdr/2013/5193.2955
|View full text |Cite
|
Sign up to set email alerts
|

Application of WHONET in the Antimicrobial Resistance Surveillance of Uropathogens: A First User Experience from Nepal

Abstract: This study, a first of its kind which was done in Nepal, was carried out by using the WHONET software to monitor, analyze and share the antimicrobial susceptibility data at various levels. This study was also aimed at building a surveillance network in Nepal, with the National Public Health Laboratory, Nepal, acting as a nodal centre. This would help in the formulation of antibiotic policies and in identifying hospital and community outbreaks at the nodal centre, as well as in sharing information with the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…Nearly 20% of E. faecium were resistant to vancomycin and 12% to Teicoplanin. In Nepal VRE in clinical isolate was reported from Manipal teaching hospital (one isolate) by disc diffusion method 54 and one VRE (MIC=32 mcg/ml) from case of peritonitis patient in a continuous ambulatory patient in B.P Koirala institute of health science 55 . These studies are probably the only available reports on clinically isolated VRE detected by agar dilution method in Nepal till date as mentioned by Amatya et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 20% of E. faecium were resistant to vancomycin and 12% to Teicoplanin. In Nepal VRE in clinical isolate was reported from Manipal teaching hospital (one isolate) by disc diffusion method 54 and one VRE (MIC=32 mcg/ml) from case of peritonitis patient in a continuous ambulatory patient in B.P Koirala institute of health science 55 . These studies are probably the only available reports on clinically isolated VRE detected by agar dilution method in Nepal till date as mentioned by Amatya et al 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Investigators from western Nepal have reported VRE by disc diffusion method however they did not confirm their findings by MIC determination. 13 Amatya et al 12 11 previously in hospital from eastern Nepal. In this study all these VIE isolates were from inpatients samples and were resistant to ampicillin, ciprofloxacin, erythromycin and HLG.…”
Section: Discussionmentioning
confidence: 98%
“…has been reported also from Nepal. [11][12][13] It does raise the question of whether the antimicrobial resistance pattern among these bacteria in Nepal has changed. Improved knowledge of local and regional epidemiology and susceptibility patterns of bacteria is crucial in order to optimize empiric antibiotic treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study high resistance percentages (88%) was reported to chloramphenicol, tetracycline, naldixic acid. However, [23] found the resistant percentages of E. coli to naldixic acid were (86%), while [22] stated that a resistance percentage of E. coli to nalidixic acid was (20%). The resistance to quinolones as naldixic acid in gram-negative bacteria such as E. coli is mainly recalled to a mutation in their chromosome which modifies the targeted enzyme of the bacterium (DNA gyrase) and topoisomerase IV, or enhnce the efflux pump system that drain the drugs out of the cytoplasm.…”
Section: E25 S R R R S R R R S S 60%mentioning
confidence: 99%